Lipsmacking imitation skill in newborn macaques is predictive of social partner discrimination. - Elizabeth A Simpson; Annika Paukner; Valentina Sclafani; Stephen J Suomi; Pier F Ferrari (PLoS ONE)
Newborn rhesus macaques imitate facial gestures even after a delay, revealing the flexible nature of their early communicative exchanges. In the present study we examined whether newborn macaques are also sensitive to the identities of the social partners with whom they are interacting. We measured infant monkeys' (n = 90) lipsmacking and tongue protrusion gestures in a face-to-face interaction task with a human experimenter in the first week of life. After a one-minute delay, the same person who previously presented gestures or a different person returned and presented a still face to infants. We had two primary predictions: (1) infants would demonstrate higher rates of overall gesturing, and especially lipsmacking--an affiliative gesture--to a familiar person, compared to a novel person, and (2) infants' imitative skills would positively correlate with gestures to familiar, but not unfamiliar, social partners, as both abilities may reflect a strong general social interest. We found that overall infants did not produce more gestures or more lipsmacking when approached by a familiar person compared to a novel person; however, we did find individual differences in infants' social responsiveness: lipsmacking imitation was positively correlated with lipsmacking during the return period when the person was the same (p = .025), but not when the person was novel (p = .44). These findings are consistent with the notion that imitative skill is reflective of infants' more general interest in social interactions.